Impact Analysis of Environmental Law Policy on Cirebon Coastal Communities in Climate Change Adaptation - MAHARDEKA, Adelia Putri; WULANDARI, Siwi; MAGFIRRO, Rosiana (Protection: Journal Of Land And Environmental Law, 2025)
Cirebon's coastal communities face intensifying climate change impacts, such as sea level rise, coastal abrasion, and natural disasters, which threaten their socio-economic resilience. Environmental law policy should be the main instrument in directing the adaptation strategies of coastal communities. However, the implementation of this policy still faces various challenges, including overlapping regulations, weak law enforcement, and lack of community participation in the policy formulation process. This research uses a qualitative approach with a case study method to evaluate the effectiveness of environmental law policies in supporting the social adaptation of Cirebon's coastal communities. Data were collected through in-depth interviews with affected communities, government officials, and policy experts, as well as analysis of related legal documents. The results showed a gap between policies and factual conditions in the field, especially in inter-agency coordination, resource allocation, and community access to environmental justice. This study emphasizes the need for environmental law policy reform that is more adaptive, ecologically just, and oriented towards empowering coastal communities in the face of climate change.